Methadone Poisoning in Children: A Systematic Review and Meta-Analysis in Iran - Yasaman Allameh; Faezeh Sadat Akrami; Gholamreza Mohammadi; Nader Molavi; Masoudeh Babakhanian (Mazandaran University of Medical Sciences, 2017)
Context: Symptoms of methadone poisoning, as one of the most dangerous types of poisoning, are very serious in children. Objectives: The aim of this study was to describe causes and clinical symptoms of methadone poisoning in children admitted to hospitals in Iran. Data Sources: Relevant studies published in national and international journals before January 29, 2016 were identified by studying the available databases, including PubMed, Web of Sciences, Google Scholar, Scopus, SID, Iranmedex, MagIran, and Irandoc. Study Selection: After excluding duplicate, irrelevant, and low-quality articles, relevant papers were entered into the meta-analysis. The prevalence, mean, and standard deviation of methadone poisoning symptoms in children were statistically analyzed, using Stata version 11, and causes of methadone poisoning were presented in tables. Data Extraction: Studies with unknown sample sizes, abstracts without access to full text, articles with quality assessment scores below 15.5, and studies carried out on non-Iranian populations were excluded from the meta-analysis. Results: During the initial advanced search, 1594 articles were identified. After quality assessment, 12 papers were found eligible for the final systematic review and meta-analysis, based on the inclusion and exclusion criteria. The reported symptoms included drowsiness, vomiting, apnea, cyanosis, seizure, ataxia, and delirium. In the meta-analysis, prevalence of symptoms in referred patients was estimated at 44% (0.95% confidence interval, 0.288 to 0.609). The causes of poisoning in children included accidental feeding by parents, storage of drugs in inappropriate containers, parental addiction, and low educational level of parents. Conclusions: It is important to keep methadone in a suitable container away from children. Also, it is essential to focus on educating parents on health issues of their children.